2020
DOI: 10.1007/s00170-020-06105-z
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic orthogonal turning of Ti-6Al-4V

Abstract: Cooling of machining operations by liquid nitrogen is a promising approach for reducing cutting temperatures, increasing tool life and improving the workpiece surface integrity. Unfortunately, the cooling fluid tends to evaporate within the supply channel. This induces process variations and hinders the use of nitrogen cooling in commercial applications. In this work, the coolant is applied via the tool’s rake face during orthogonal turning of Ti-6Al-4V. The effect of a nitrogen supply pressure adjustment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…However, the machining costs were found to increase as the flow rate increased. Moreover, Stampfer et al [ 65 ] concluded that machining forces and cutting tool temperatures were reduced by using high-pressure cryogenic coolant (nitrogen) supply on orthogonal turning of titanium alloy. Also, the tool wears on internal rake face of the cutting tool were reduced under cryogenic cooling compared to dry cutting.…”
Section: Types Of Coolant Deliverymentioning
confidence: 99%
“…However, the machining costs were found to increase as the flow rate increased. Moreover, Stampfer et al [ 65 ] concluded that machining forces and cutting tool temperatures were reduced by using high-pressure cryogenic coolant (nitrogen) supply on orthogonal turning of titanium alloy. Also, the tool wears on internal rake face of the cutting tool were reduced under cryogenic cooling compared to dry cutting.…”
Section: Types Of Coolant Deliverymentioning
confidence: 99%
“…As a countermeasure insulated pipes, insulated tools or a phase separator are usually used, however their effectiveness is questionable. Attractive alternative is subcooling, a known principle when LN2 is used to cool silicone chips in microelectronics which was recently proposed in the application of cryogenic cutting [21], (Fig. 5).…”
Section: High Performance Cooling Techniques 21 Cryogenic Machiningmentioning
confidence: 99%
“…5. Setup of the nitrogen supply with subcooler and comparison of standard nitrogen supply (red line) and the subcooler case (blue line) [21] Subcooler usage decreases the nitrogen evaporation rate and accelerates the initial cooling of the supply system. Therefore, increased mass flow rates result at the same working pressures, compared to systems without subcooling.…”
Section: High Performance Cooling Techniques 21 Cryogenic Machiningmentioning
confidence: 99%